Early Population Dynamics of “Candidatus Liberibacter asiaticus” in Susceptible and Resistant Genotypes After Inoculation With Infected Diaphorina citri Feeding on Young Shoots - Alves, Mônica Neli; Cifuentes-Arenas, Juan Camilo; Raiol-Junior, Laudecir Lemos; Ferro, Jesus Aparecido; Peña, Leandro (Frontiers in Microbiology, 2021)
Huanglongbing is a highly destructive citrus disease associated with “Candidatus Liberibacter asiaticus” (Las), a phloem−limited and non-culturable bacterium, naturally transmitted by the psyllid Diaphorina citri. Although diverse approaches have been used to understand the molecular mechanisms involved in the pathogen–host interaction, such approaches have focused on already infected and/or symptomatic plants, missing early events in the initial days post-inoculation. This study aimed to identify the time course of Las multiplication and whole-plant colonization immediately following inoculation by infected psyllids feeding for 2 days. Thus, the experimental approach was to track Las titers after psyllid inoculation in new shoots (NS) of Citrus × sinensis (susceptible), Murraya paniculata (partially resistant), and Bergera koenigii (fully resistant). Soon after psyllid removal, Las titers dropped until the 10–12th days in all three species. Following this, Las titers increased exponentially only in C. × sinensis and M. paniculata, indicating active bacterial multiplication. In C. × sinensis, Las reached a stationary phase at ∼5 log Las cells/g of tissue from the 40th day onward, while in M. paniculata, Las increased at a lower rate of up to ∼3 log Las cells/g of tissue between the 40th and 60th days, decreasing gradually thereafter and becoming undetectable from the 160th day onward. In B. koenigii, Las titers decreased from the start and remained undetectable. In C. × sinensis, an average of 2.6 log of Las cells/g of tissue was necessary for Las to move out of 50% of the NS in 23.6 days and to colonize the rest of the plant, causing a successful infection. Conversely, the probability of Las moving out of the NS remained below 50% in M. paniculata and zero in B. koenigii. To our knowledge, this is the first study on Las dynamics and whole-plant colonization during the earliest stages of infection. Identification of critical time-points for either successful multiplication or Las resistance may help to elucidate initial events of Las–host interactions that may be missed due to longer sampling intervals and at later stages of infection.